An examination of the variation in maternal placentae across the genus Poeciliopsis (Poeciliidae). (12th March 2015) - Kwan, Lucia; Fris, Megan; Rodd, F. Helen; Rowe, Locke; Tuhela, Laura; Panhuis, Tami M.
ABSTRACT Placentae show considerable diversity in a number of nonmammalian, viviparous organisms, including amphibians, reptilian sauropsids, teleost fish, and chondrichthyes. However, the evolutionary processes driving the evolution of placenta are still debated. In teleost fishes, the genus Poeciliopsis (Poeciliidae) offers a rare opportunity for studying placental evolution: extensive placentation has evolved three independent times within the last 750, 000 years and there is substantial interspecific variation in the degree of embryonic, maternal nutrient provisioning and development of the placenta. In poeciliids, the placenta is composed of a hypertrophied maternal follicular epithelium apposed to a highly vascularized embryonic pericardial sac. To better understand placental evolution, we have undertaken a comprehensive comparative study of the maternal follicle in eight closely related Poeciliopsis species that span the range in postfertilization, embryonic, maternal nutrient provisioning (from lecithotrophs, to moderate matrotrophs, to extensive matrotrophs). Using light and scanning electron microscopy, we found that the species that provide extensive postfertilization maternal nutrient provisioning (extensive matrotrophs) have thicker follicles and more extensive folding of the follicular epithelium compared to the lecithotrophs and moderate matrotrophs. Follicle sections and histology revealed that epithelial folds of the extensive matrotrophs are comprised primarily of cuboidal and columnar cells and are richly supplied with capillaries. Among the extensive matrotrophs, enhancements of follicle traits corresponded with increases in the level of maternal nutrient provisioning. Hypertrophied maternal follicles with richly vascularized folds can serve to increase the surface area and, thus, facilitate the transfer of substances between the mother and developing embryo. Finally, we found egg envelopes in the lecithotrophs and moderate matrotrophs, but not in the extensive matrotrophs. Morphological studies, like this one, can provide a better understanding of the natural variation in the structure and functioning of maternal and offspring traits associated with matrotrophy and, thus, insights into the processes driving placental evolution. J. Morphol. 276:707–720, 2015. © 2015 Wiley Periodicals, Inc.